International Business Administration, Management Program Faculty of Economics and Business - Tumilaar, Priskila O.; Saerang, David P. E.; Tumbuan, Willem J. F. A (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
PT. Gudang Garam Tbk is one of the leading cigarette industries in Indonesia that was founded in 1958 in the city of Kediri, East Java. The aim of this research is to analyzing the marketing mix of PT. Gudang Garam Tbk by using Importance and Performance analysis. Marketing mix is a combination of factors that can be controlled by a company to influence people to purchase its products. Marketing Mix divided into 7P’s which are product, price, promotion, place, process, physical evidence. This research based on samples that are 100 respondents who consumed PT. Gudang Garam’s Product in Manado. This research is using Importance and Performance Analysis with IBM SPSS Statistic. The meeting point of Importance (Y) and Performance (X) of each attribute will determined where to place the attribute among 4 quadrants in IPA (Importance and Performance Analysis) matrix to know how well PT. Gudang Garam, Tbk in Manado deliver their performance on Marketing Mix. Based on this research, researcher found that PT. Gudang Garam Tbk overall not deliver good performance on marketing mix because there are eight attributes found in quadrant I which is consumer found extremely important but the company only give fair performance. Keywords: Marketing mix, importance and performance analysis